New Evidence of Environmental Kuznets Curve Hypothesis in Developing Countries - Vita Kartika Sari; Aulia Hapsari Juwita; Malik Cahyadin (Muhammadiyah University Press, 2021)
New indexes of environment and institutions are constructed following principal component analysis (PCA), while non-linear panel regression is employed. This study attempts to estimate a non-linear impact of GDP per capita on the environment following the Environmental Kuznets Curve (EKC) Hypothesis for 97 developing countries during 1991-2014. The study reveals that a traditional EKC shows a U-shaped relationship under static panels, with both quadratic and cubic regressions. Interestingly, the inverted U-shaped occurs when a traditional EKC is estimated by the dynamic panels, with both quadratic and cubic regressions. Moreover, the EKC model is inverted U-shaped following static and dynamic panels, with both quadratic and cubic regressions under institutions. Indeed, the institutions significantly contribute to express EKC in developing countries. Policymakers should formulate environmental policies following climate change mitigation in the environmental sustainability framework, improve the quality of institutions, and increase macroeconomic management to anticipate external shocks such as openness, globalization, and FDI inflows.